2019
DOI: 10.1111/jnc.14710
|View full text |Cite
|
Sign up to set email alerts
|

α‐synuclein oligomers enhance astrocyte‐induced synapse formation through TGF‐β1 signaling in a Parkinson's disease model

Abstract: Parkinson's disease (PD) is characterized by selective death of dopaminergic neurons in the substantia nigra, degeneration of the nigrostriatal pathway, increases in glutamatergic synapses in the striatum and aggregation of α‐synuclein. Evidence suggests that oligomeric species of α‐synuclein (αSO) are the genuine neurotoxins of PD. Although several studies have supported the direct neurotoxic effects of αSO on neurons, their effects on astrocytes have not been directly addressed. Astrocytes are essential to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 88 publications
0
27
0
Order By: Relevance
“…Recently, Bosson et al (2015) reported an increase in the number of glutamatergic synapses, which was accompanied by alterations in astrocytic morphology in the SNr of a rat model to PD. Moreover, intracerebroventricular injection of α-syn increased the number of astrocytes, the density of excitatory synapses, and the levels of TGF-b1 in the striatum of injected animals (Diniz et al, 2019). Similarly, astrocytic spatial territories were found to be larger in the striatum of parkinsonian monkeys (Villalba and Smith, 2011), suggesting that astrocytic remodeling is a compensatory mechanism aiming to decrease the high extracellular glutamate levels and overall neuronal hyperactivity observed in PD.…”
Section: Parkinson's Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…Recently, Bosson et al (2015) reported an increase in the number of glutamatergic synapses, which was accompanied by alterations in astrocytic morphology in the SNr of a rat model to PD. Moreover, intracerebroventricular injection of α-syn increased the number of astrocytes, the density of excitatory synapses, and the levels of TGF-b1 in the striatum of injected animals (Diniz et al, 2019). Similarly, astrocytic spatial territories were found to be larger in the striatum of parkinsonian monkeys (Villalba and Smith, 2011), suggesting that astrocytic remodeling is a compensatory mechanism aiming to decrease the high extracellular glutamate levels and overall neuronal hyperactivity observed in PD.…”
Section: Parkinson's Diseasementioning
confidence: 91%
“…PD is the second most common neurodegenerative disease (de Lau and Breteler, 2006) with symptoms including resting tremor and bradykinesia (Salarian et al, 2007). PD is characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and the formation of α-syn deposits known as Lewy bodies (Kordower et al, 2013;Diniz et al, 2019). Recently, Bosson et al (2015) reported an increase in the number of glutamatergic synapses, which was accompanied by alterations in astrocytic morphology in the SNr of a rat model to PD.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Furthermore, a common pathologic feature in both NDDs and SCI is reactive astrocytes, which are characterized as high-expressed EGFR astrocytes with high levels of activated EGFR (Liu and Neufeld, 2004;Zhang and Neufeld, 2005;Liu et al, 2006;Liu and Neufeld, 2007;Chen et al, 2017). Stimulations such as injuries, genetic mutations in familial NDDs (Booth et al, 2017;Frost and Li, 2017;González-Reyes et al, 2017;Ceyzériat et al, 2018;Joe et al, 2018;Perez-Nievas and Serrano-Pozo, 2018), and amyloid fibrils (Forman et al, 2005;Kahlson and Colodner, 2015;Chavarría et al, 2018;Diniz et al, 2019;Lohmann et al, 2019;Tremblay et al, 2019) can induce a reactive astrocytes condition, which finally leads to neurodegeneration. Considering the beneficial effect of EGFR inhibition in neurodegenerative diseases and treatment of reactive astrocytes pathology in SCI, there is an essential need to clarify the role of EGFR activation in noncancer brain pathologies as well as molecular pharmacology of EGFR inhibition as a novel therapy for both NDDs and SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, astrocytes and microglia have been shown to possess a duality (or, probably multiplicity) in their phenotype, which can shift between "neuroprotective" and "neurotoxic" properties, depending on stimuli, and physiological/pathological condition. [146][147][148] As a consequence of activation by various stimuli, microglial cells and astrocytes shift to a pro-inflammatory phenotype, which increases the release of cytokines, chemokines, and neurotoxic factors thus promoting immune stimulation, neuroinflammation and CNS dysfunction. 149,150 This activation has been shown to be able to foster a self-perpetuating hyper-response: previous encounters of inflammatory stimuli will "prime" the glial compartment for an exaggerated response to subsequent challenges.…”
Section: Evidence #mentioning
confidence: 99%